The Little-Known yet Storied Past Linking Oman and Zanzibar - Bodetti, Austin (Inside Arabia, 2021)
Only a few scholars have explored the shared past of Oman and Zanzibar. Nonetheless, culture, history, and religion continue to bind the two.
Keywords: Relations -- Oman -- Afrique de l'Est